PENGARUH PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Asfi Yuhani; Luvy Sylviana Zanthy; Heris Hendriana (IKIP Siliwangi, 2018)
Problem-solving ability is the ability to solve non-routine problems related to everyday life. Problem-solving learning more focuses on processes and strategies. So the process skills and strategies for solving a problem become the essential capability that must be owned in mathematics learning. The purpose of this study is to know the effect of problem-based learning approach to the problem-solving ability of junior high school students. The research method used in this research is the experimental method. The population taken in this research is all of VII grade student SMP Negeri 2 Cimahi. As a sample, the researcher took a random class, where grade VII-1 with the number of 34 students was used as the experimental class and class VII-2 with the total of 34 students used as control class. The instrument used in this research that is in the form of problem description of problem-solving ability mathematics consists of 5 item. The results of this study indicate that the problem-solving ability of the mathematical group of students whose learning using problem-based learning approaches better than the group of students whose learning using ordinary learning.